Designing Change in Organizations: A Systematic Literature Review of Intuition-Based Transformational Leadership in Islamic School Management - Novriyanto, Erwin; Hidayat, Rais (Universitas Syiah Kuala, 2025)
Changes in educational organizations are inevitable in the midst of external dynamics that continue to develop. In the context of community-based Islamic schools, organizational change requires not only a structural strategy, but also a values-laden and spirituality approach. Transformational leadership is considered relevant in directing change because it is able to build long-term vision, innovation, and empowerment. When combined with intuition as a reflective instrument in decision-making, this approach has the potential to result in meaningful and sustainable transformation. This study aims to systematically synthesize the scientific literature on the integration of transformational leadership and intuition in the management of organizational change in Islamic educational institutions. The method used is Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines, which produced 14 relevant and valid scientific articles. The results of the study show that intuition-based transformational leadership is able to accelerate the adoption of change, build organizational trust, and increase stakeholder participation. Leadership practices in Islamic schools have peculiarities in aspects of spirituality, exemplary, and community culture. This study contributes to the development of educational leadership models that are contextual, reflective, and adaptive to the dynamics of change, as well as enriching the treasure of Islamic education management literature.